Mentoring Management Tourism Village Finance Johar Embankment for Increase Accountability and Independence of Village- Based Economy Technology - Fenny Afrida; Fachrul A. Siregar; Taufiqurrahman Taufiqurrahman; Muhammad Hafiz Abd.Rashid; Sipnarong Kanchawongpaisan; Cindi Kosasi (Eastasouth Journal of Effective Community Services, 2025)
Tourism Village Johar Embankment is experiencing improvement activity economy along increase visit tourists, but governance​ his finances Still face constraint like manual recording, low competence managers, and the lack of transparency. Devotion This aim increase accountability and independence economy village through mentoring management finance-based technology. The method used is studies case with approach descriptive qualitatively equipped​ observation, interviews, documentation, and mentoring directly. Activities done through five stages: assessment initial, SOP preparation, training application finance, implementation digital recording, and evaluation impact. The results show improvement competence management, implementation of new SOPs, use more digital recording orderly, and increasing transparency reporting finance. Mentoring This push change behavior administration, emergence leader local, and strengthening potential independence economy village tour.